Utility of atherosclerosis-associated serum antibodies against colony-stimulating factor 2 in predicting the onset of acute ischemic stroke and prognosis of colorectal cancer - Li, Shu-Yang; Yoshida, Yoichi; Kubota, Masaaki; Zhang, Bo-Shi; Matsutani, Tomoo; Ito, Masaaki; Yajima, Satoshi; Yoshida, Kimihiko; Mine, Seiichiro; Machida, Toshio; Hayashi, Aiko; Takemoto, Minoru; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Autoantibodies against inflammatory cytokines may be used for the prevention of atherosclerosis. Preclinical studies consider colony-stimulating factor 2 (CSF2) as an essential cytokine with a causal relationship to atherosclerosis and cancer. We examined the serum anti-CSF2 antibody levels in patients with atherosclerosis or solid cancer. Methods: We measured the serum anti-CSF2 antibody levels via amplified luminescent proximity homogeneous assay-linked immunosorbent assay based on the recognition of recombinant glutathione S-transferase-fused CSF2 protein or a CSF2-derived peptide as the antigen. Results: The serum anti-CSF2 antibody (s-CSF2-Ab) levels were significantly higher in patients with acute ischemic stroke (AIS), acute myocardial infarction (AMI), diabetes mellitus (DM), and chronic kidney disease (CKD) compared with healthy donors (HDs). In addition, the s-CSF2-Ab levels were associated with intima-media thickness and hypertension. The analyses of samples obtained from a Japan Public Health Center-based prospective study suggested the utility of s-CSF2-Ab as a risk factor for AIS. Furthermore, the s-CSF2-Ab levels were higher in patients with esophageal, colorectal, gastric, and lung cancer than in HDs but not in those with mammary cancer. In addition, the s-CSF2-Ab levels were associated with unfavorable postoperative prognosis in colorectal cancer (CRC). In CRC, the s-CSF2-Ab levels were more closely associated with poor prognosis in patients with p53-Ab-negative CRC despite the lack of significant association of the anti-p53 antibody (p53-Ab) levels with the overall survival. Conclusions: s-CSF2-Ab was useful for the diagnosis of atherosclerosis-related AIS, AMI, DM, and CKD and could discriminate poor prognosis, especially in p53-Ab-negative CRC.